2015
DOI: 10.1152/ajprenal.00051.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic kidney disease induced by adenine: a suitable model of growth retardation in uremia

Abstract: Growth retardation is a major manifestation of chronic kidney disease (CKD) in pediatric patients. The involvement of the various pathogenic factors is difficult to evaluate in clinical studies. Here, we present an experimental model of adenine-induced CKD for the study of growth failure. Three groups (n = 10) of weaning female rats were studied: normal diet (control), 0.5% adenine diet (AD), and normal diet pair fed with AD (PF). After 21 days, serum urea nitrogen, creatinine, parathyroid hormone (PTH), weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 23 publications
5
37
0
Order By: Relevance
“…3 Additionally, in patients with primary hyperparathyroidism, lumbar vertebral bone mineral content was reported to be increased, whereas bone mineral density of the radius was found to be decreased. 21 Furthermore, increases in tibial and femoral trabecular BV/TV have been reported in mouse 19,20 and rat 22,23 models of kidney disease with secondary hyperparathyroidism as well as in vertebrae of rats treated with continuous PTH infusions. 24 These reports support the impression that in the model reported here, hyperparathyroidism led to the observed bone phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…3 Additionally, in patients with primary hyperparathyroidism, lumbar vertebral bone mineral content was reported to be increased, whereas bone mineral density of the radius was found to be decreased. 21 Furthermore, increases in tibial and femoral trabecular BV/TV have been reported in mouse 19,20 and rat 22,23 models of kidney disease with secondary hyperparathyroidism as well as in vertebrae of rats treated with continuous PTH infusions. 24 These reports support the impression that in the model reported here, hyperparathyroidism led to the observed bone phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…The control group was fed standard chow, while the other two groups were fed 0.5% adenine (Sigma-Aldrich, St. Louis, MO, USA) chow for 3 weeks to induce chronic renal failure [37, 38]. After the models were successfully made, rats in control and model groups received saline in the amount of 20 ml/kg/d, while those in FSGD group received 16 g/kg/d, administered by gastric irrigation, respectively, for 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…The 0.25% adenine diet was also used as a model for CKD in mice either for 10 days or for 4 weeks . Another study demonstrated similar CKD responses, however, with a higher (0.5%) dose of adenine for 3 weeks which approximates to only 1.5 years in humans . Kidney disease was established with 0.2% adenine for 4 weeks in C57 BL6 mice .…”
Section: Optimising the Adenine Model Of Ckdmentioning
confidence: 98%